Analysis Of Company Reputation and Product Innovation Against Marketing Performance Through Competitive Advantage at PT Amanah Travel Indonesia - Erlina Satrin NY; Mesra B; Elfitra Desy Surya (International Journal of Management, Economic and Accounting, 2025)
This study aims to test and analyze the influence of company reputation and product innovation on competitive advantage in PT Amanah Travel Indonesia. To test and analyze the influence of company reputation and product innovation on marketing performance at PT Amanah Travel Indonesia through competitive advantage. The method used in this study is a quantitative method. Data analysis techniques using SMART PLS. Data collection techniques using Quesioner and interviews. Using the slovin formula, a sample of 160 consumers was obtained. The results of the study show that the company's reputation and product innovation have a positive and significant effect on the competitive advantage of PT Amanah Travel Indonesia. The company's reputation and product innovation to the marketing performance of PT Amanah Travel Indonesia through competitive advantage.